The critical role of toll-like receptor 4 in bone remodeling of osteoporosis: from inflammation recognition to immunity - Zhu, Xianping; Du, Li; Zhang, Lai; Ding, Lingzhi; Xu, Weifang; Lin, Xuezheng (Frontiers in Immunology, 2024)
Osteoporosis is a common chronic metabolic bone disorder, representing a worldwide formidable healthcare challenge. New targets for osteoporosis prevention and treatment have become an important endeavor. Recently, mounting increasing numbers of studies have demonstrated that Toll-like receptor 4 (TLR4, a receptor located on the surface of osteoclasts and osteoblasts) plays a pivotal role in the development of osteoporosis.Herein, we performed a first attempt a comprehensive review to summarize the findings from the relevant studies within this topic through a comprehensive review. Clinical data showed that TLR4 polymorphisms and aberrant expression of TLR4 TLR4 expression have been associated with the clinical significance of osteoporosis in clinical practice. Mechanistically, dysregulation of osteoblasts and osteoclasts induced by abnormal expression of TLR4 is the main molecular mechanism underlying TLR4mediated the pathological processes of osteoporosis, which may be associated with the interactions between TLR4 and NF-κB pathway, proinflammatory effects, ncRNAs, and RUNX2. In vivo and in vitro studies demonstrate that many promising compounds substances or agents (i.e., methionine, dioscin, miR-1906 mimic, artesunate, AEG-1 deletion, patchouli alcohol, and Bacteroides vulgatus) have been able to improve bone metabolism (i.e., inhibits bone resorption and promotes bone formation), which may partially attribute to the inhibition of TLR4 expression. The present review highlights the important role of TLR4 in the clinical significance and the pathogenesis of osteoporosis from the aspects of inflammation and immunity. Future therapeutic strategies targeting TLR4 might may provide a new insight for osteoporosis treatment.